Tumor-targeted delivery of sunitinib base enhances vaccine therapy for advanced melanoma by remodeling the tumor microenvironment - Huo, Meirong; Zhao, Yan; Satterlee, Andrew Benson; Wang, Yuhua; Xu, Ying; Huang, Leaf (Journal of controlled release, 2017)
Development of an effective treatment against advanced tumors remains a major challenge for cancer immunotherapy. We have previously developed a potent mannose-modified lipid calcium phosphate (LCP) nanoparticle (NP)-based Trp2 vaccine for melanoma therapy, but because this vaccine can induce a potent anti-tumor immune response only during the early stages of melanoma, poor tumor growth inhibition has been observed in more advanced melanoma models, likely due to the development of an immune-suppressive tumor microenvironment (TME). To effectively treat this aggressive tumor, a multi-target receptor tyrosine kinase inhibitor, sunitinib base, was efficiently encapsulated into a targeted polymeric micelle nano-delivery system (SUNb-PM), working in a synergistic manner with vaccine therapy in an advanced mouse melanoma model. SUNb-PM not only increased cytotoxic T-cell infiltration and decreased the number and percentage of MDSCs and Tregs in the TME, but also induced a shift in cytokine expression from Th2 to Th1 type while remodeling the tumor-associated fibroblasts, collagen, and blood vessels in the tumor. Additionally, inhibition of the Stat3 and AKT signaling pathways by SUNb-PM may induce tumor cell apoptosis or decrease tumor immune evasion. Our findings indicated that targeted delivery of a tyrosine kinase inhibitor to tumors can be used in a novel synergistic way to enhance the therapeutic efficacy of existing immune-based therapies for advanced melanoma. [Display omitted]